The impact of AI-based painting technology on children’s creative thinking - Wang, Anna; Zhang, Yuxin; Wang, Anman; Zheng, Wei (Frontiers in Psychology, 2025)
With the emerging application of artificial intelligence (AI) in education, AI-based painting technology has been fully introduced into the development of children’s creative thinking. However, the following studies mainly focus on the technological development and system optimization. There are concerns on the limited educational perspectives, sampling biases, and imperfect theoretical frameworks which restrict the effective evaluation on the AI tools and children’s art education. In this paper, we conduct a systematic review and examines the multidimensional impacts of AI-based painting tools on children’s creative thinking, including the creative expression, original creation, independent thinking and problem solving. With the PRISMA guidelines, we analysis 20 empirical articles (14 from Scopus and Web of Science and 6 from other sources) and provide recommendations on how educators can effectively integrate these tools into art education to foster children’s creative thinking. We find that AI tools enhance creative expression through virtual interaction and personalized learning. However, there are still risks of cognitive homogenization due to standardized interfaces and the disconnection between theory and practice. Our study propose evidence-based strategies for educators to select age-appropriate tools and implement process-oriented assessments. We also advocate the application of technology from educational and humanistic perspectives to balance technical effectiveness and humanistic educational goals.